Tantangan dan Peluang Implementasi ESG di Bank Syariah - Selvia Della Yunitasari; Marendi Dwi Saputra; Salsabilla Ardi Agustin; Chrestalia Danesya putri (MONETARIUM: Journal of Economics Business and Management, 2025)
The development of the Environmental, Social, and Governance (ESG) concept has had a significant impact on the direction of global financial policies and practices, including in the Islamic banking sector. ESG is in line with Sharia principles that emphasize the values of justice, social responsibility, and sustainability in all economic activities. This study aims to analyze the challenges and opportunities of ESG implementation in Islamic banks using a literature review method. Data were obtained from various scientific sources, such as academic journals, reports from the Financial Services Authority (OJK), as well as official documents related to ESG practices in Islamic finance. The research results show that the main challenges of ESG implementation in Islamic banks include a lack of understanding of ESG concepts, limited human and technological resources, and the absence of specific reporting standards that align with Sharia principles. However, on the other hand, there are significant opportunities for Islamic banks through government regulatory support, the alignment between ESG and maqasid sharia, and the growing interest of investors in sustainable financial products such as green sukuk. ESG implementation that is in harmony with Islamic values is expected to strengthen the competitiveness, reputation, and role of Islamic banks in realizing sustainable finance in Indonesia.